Ordinance No. 8, Div. 1, §§ 4-5 & Div. 3, § 1, Arlington Town Council (1903) (Arlington, Washington). - (:unkn) unknown (My University, 1902)
Whoever shall, within the town of Arlington, carry or wear under his or her clothes, or conceal about the person, any dangerous or deadly weapon, shall be fined in any sum not exceeding one hundred dollars, or be imprisoned not exceeding thirty days, or be both fined and imprisoned.Whoever shall, within the town, draw any species of fire arms, or any dirk, dagger, knife or other dangerous or deadly weapon on the person of another, shall be subject to a fine of not less than five dollars, and not exceeding one hundred dollars, or be imprisoned not exceeding thirty days, or be both fined and imprisoned. Whoever shall fire or discharge any cannon, gun, pistol, revolver or any fire arm of any description, or shall fire or explode, or set off any squib, fire cracker, torpedo or other thing containing powder or other explosive material, without permission from the town marshall or town council so to do, within the corporate limits. Provided that such permission, when given, shall definitely limit the time of such firing and may at any time be revoked; but nothing in this section shall prevent the ordinary and usual fire works demonstration on national holidays, subject, however, to such regulations, control and order as the marshal may deem proper to make for the protection of property from fire."
Keywords: BRANDISHING; CARRY - CONCEALED; DISCHARGE